Studi Living Qur'an dalam Tradisi Air Purnama di Desa Lontar Tirtayasa, Kabupaten Serang - Sulistiawati Taning Asih; Sholahuddin Al Ayubi; Mus’idul Millah; Muhammad Sapi’i (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This research is based on the existence of the Living Qur’an phenomenon in Lontar village, Tirtayasa district, Serang Banten district, which is the Purnama Water Tradition. This tradition is one of the religious rituals carried out by the Lontar community, which is subsequently performed by the local community as a ritual aimed at calming the heart. (Padang ati). In this tradition, the signs of the Qur'an are used as a medium of healing and water as its medium. The study aims to analyze the processes and practices of the water traditions and the perception of the community towards the water tradition. The method used in writing this research is entographic research with the theory of al-Qur’an reception developed by Ahmad Rafiq. Data collection involves in-depth interviews with key figures, observations, and document studies. The results of this study show that the water that has been prayed is believed to cure a variety of disorders or diseases, both medical and non-medical, commonly referred to as ruqyah. According to some sources, the full moon is also believed to have its privilege. So from that, this tradition is done on Friday night, on the 15th of the month of hijrah, and exactly when the full moon rises.